Early Laparoscopic Cholecystectomy in acute cholecystitis and its sequlae: Experience in tertiary care hospital - Ratan, Md Ezharul Haque; Alam, Hasina (Bangladesh Critical Care Journal, 2017)
Background: Acutecholecystitis (AC) is a common surgical condition requiring emergency hospitalization. Traditionally, these patients were treated conservatively, followed by delayed surgery six weeks or longer after acute event has subsided. Recently, early emergency cholecystectomy at same admission is suggested. This has the advantage of reduced length of stay (LOS) in hospital without any significant increase in complication rate. Moreover, conservative management is not always successful. We are here, observing the feasibility of emergency cholecystectomy in practical setting. Method: Between March 2008 and March 2017, 483 patients were admitted in a surgical unit of BIRDEM general hospital with the diagnosis of acute cholecystitis or its complications. The patients were assessed clinically with laboratory and imaging investigations. We planned early laparoscopic cholecystectomy (ELC) in all case, as soon as assessment and resuscitation were completed, irrespective of duration from symptom onset. Cases were analyzed for gender, age, operation time, volume of blood loss, conversion to open surgery, post-operative complication and length of hospital stay. Results: A total of 483 patients with AC and its sequlae were admitted, between March 2008 and March 2017 in a single unit of a tertiary care hospital which deals most of the diabetic patients of the country. Among them 477 patients were treated with emergency or urgent laparoscopic cholecystectomy (LC). The earlier the patient presented for surgery and those who were treated with antibiotics were easier to operate. Incidence of gangrene and perforation were more among those with acalculus cholecystitis. Surgical procedures were the most difficult in those presented beyond two weeks of symptom onset. Consequently operation time was over 100 minutes and blood loss was more than 250ml in such cases. Fortunately none required conversion to open procedure. Subhepatic drain were used in 17 cases. Subcutaneous simple tube drain in umbilical port was used in those with gangrene, perforation and transmural gall bladder wall pyogenic infection. Consequently umbilical port infection were very low (3cases, 0.6%). One patient presented with subhepatic fluid collection, 6 weeks after emergency LC. Laparotomy was done and found to have altered blood and pseudo-aneurysm of cystic artery (chronic blood loss from one of its lateral twig). Length of stay (LOS) in hospital were short (mean-1.8days, range: 20hours-4 days) except those with bile leak (5, 8 and 9 days respectively). None of the cases had bile duct injury or uncontrolled bleeding. There was no mortality in this series. Conclusion: Early laparoscopic cholecystectomy (ELC) has proved to be an effective and safe day case surgical procedure for AC and their complications. It provides much benefits with low complication and conversion in experienced hands. Bangladesh Crit Care J September 2017; 5(2): 101-105